2019
DOI: 10.1111/1462-2920.14499
|View full text |Cite
|
Sign up to set email alerts
|

A metatranscriptomics‐based assessment of small‐scale mixing of sulfidic and oxic waters on redoxcline prokaryotic communities

Abstract: Summary Lateral intrusions of oxygen caused by small‐scale mixing are thought to shape microbial activity in marine redoxclines. To examine the response of prokaryotes to such mixing events we employed a shipboard mixing experiment in the euxinic central Baltic Sea: oxic, nitrate containing and sulfidic water samples without detectable oxygenized substances were incubated directly or after mixing. While nitrate, nitrite and ammonium concentrations stayed approximately constant in all incubations, we observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 59 publications
(84 reference statements)
1
15
0
Order By: Relevance
“…In this view, the enhanced turbidities are interpreted as the optical signature of colloidal sulfur particles generated during the mixing of oxic and sulfidic waters (Schmale et al ; Holtermann et al ), similar to the classical redoxcline turbidity peak found in the Baltic Sea and other euxinic systems (Blumenberg et al ; Wakeham et al ; Jakobs et al ). This is consistent with a recent study of Beier et al (), who investigated the microbiological consequences of permanent small‐scale intrusions into the anoxic deep layers of the Gotland Basin. These authors describe an unexpected upregulation of oxygen‐dependent genes in regions where neither oxygen nor oxygenated compounds such as nitrate and nitrite could be detected.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this view, the enhanced turbidities are interpreted as the optical signature of colloidal sulfur particles generated during the mixing of oxic and sulfidic waters (Schmale et al ; Holtermann et al ), similar to the classical redoxcline turbidity peak found in the Baltic Sea and other euxinic systems (Blumenberg et al ; Wakeham et al ; Jakobs et al ). This is consistent with a recent study of Beier et al (), who investigated the microbiological consequences of permanent small‐scale intrusions into the anoxic deep layers of the Gotland Basin. These authors describe an unexpected upregulation of oxygen‐dependent genes in regions where neither oxygen nor oxygenated compounds such as nitrate and nitrite could be detected.…”
Section: Discussionsupporting
confidence: 92%
“…These authors describe an unexpected upregulation of oxygen‐dependent genes in regions where neither oxygen nor oxygenated compounds such as nitrate and nitrite could be detected. Beier et al () argue that the most likely explanation for the puzzling transcription of denitrifying and sulfur oxidizing genes in the anoxic/sulfidic region below the HTZ is a permanent stimulation by intrusions.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatic analyses followed previously published protocols 67 except that metatranscriptome reads were mapped onto the BARM metagenome 41 with very sensitive settings. The recovery rate of the internal standard molecules in the sequencing data reads was used to calculate the absolute number of transcripts that were in the respective water samples 68,69 . The above described HMM search was used to identify potential bacteroidetal PETase genes in the BARM metagenome and compared to those which showed expression in the Baltic Sea metatranscriptome data set.…”
Section: Databases Used In This Study and Bioinformatic Analysismentioning
confidence: 99%
“…Differential expression analyses were made for both the PE and BAC metatranscriptome data using the DESeq2 (Love et al, 2014) package in R (version 3.4.4), with the internal standards (controlGenes) in the estimateSizeFactors function to normalize counts between samples ( Supplementary Table 3) (Beier et al, 2018). Transcriptional changes of enzymes refer to relative log2 fold changes between contrasted timepoints (including triplicates), at an adjusted p < 0.01, unless otherwise stated ( Supplementary Tables 5, 7).…”
Section: Statistics and Internal Standardsmentioning
confidence: 99%
“…Bacterial absolute transcript counts per mL (grouped by SEED Rank3), calculated according to formula in Satinsky et al (2013) can be found in Supplementary Table 6. To account for transcript length, counts were normalized to one mRNA standard at a time: pTZ19R (546nt), pFN19R (970nt) from which the mean was calculated (Beier et al, 2018), and then log2 transformed. Bacterial absolute transcript counts per mL (grouped by SEED Rank3), with standard errors (SE), calculated according to formula in Satinsky et al (2013) can be found in Supplementary Table 6.…”
Section: Nitrogen Acquisitionmentioning
confidence: 99%